The Influence of Media Innovation Application Suno AI Song Animals on Creativity Ability in Children Aged 5-6 Years - Wardani, Dzikrina Revitania; Fachurrazi, Ahmad (JOYCED: Journal of Early Childhood Education, 2025)
Early childhood is the period of the best abilities between the ages of 0-6 years, which experiences abilities and growth by providing educational stimulation that covers all aspects of the child's abilities. to prepare for further education. Suno AI Application Innovation Media Animal Songs on Creativity in Children Aged 5-6 Years The songs are designed to meet the various characteristics of early childhood, especially the unique, active and energetic, explorative and adventurous characters, and cognitive abilities in children aged 4-6 years. Media Innovation Application Suno AI Animal Songs on Creativity in Children Aged 5-6 Years Animal songs are a means to stimulate children's cognitive abilities in critical thinking and high imagination. Therefore, researchers conducted quantitative research using experimental methods and design. non-equivalent or "one group pre-test and post-test design". The sampling technique is saturated sampling and the data collection technique uses documentation and observation. The data analysis technique is carried out by hypothesis testing using the t-test. The results of the analysis show that the calculated t value of 13.5 is greater than the t table of 1.76 with a significance level of 0.05 with N = 15 which means the hypothesis null hypothesis (Ho) is rejected and the working hypothesis (H₁) is accepted. This proves that the innovation media Suno AI application Animal songs have a very significant influence on the creativity abilities of children aged 5-6 years.